เหยื่อข่มขืนหญิงในโลกทัศน์ของพนักงานสอบสวนชาย - วิชชุตา อิสรานุวรรธน์ (จุฬาลงกรณ์มหาวิทยาลัย, 2009)
To study the understanding of male investigators on female rape victims, the investigation procedures and the problems in protecting female rape victims’ rights. This study is a documentary and qualitative research, that used in-depth interview, and participating observation techniques in collecting data from 10 male investigators and 4 female rape victims whom got advices and supported by The Friends of Women Foundation. The results showed that male investigators and female rape victims defined female rape victims in different meanings both of the meaning toward being female rape victim and the rape situations and impacts, which influenced to the effectiveness of rape investigation procedures. More than that the research found that, in routine action, male investigators have knowledge, understanding and conforming the process which laws provided, including the Penal Code and the Criminal Procedure Code, but however, they should increasing their commitments to The Regulatory Framework Tool about rape investigation procedures established by the Royal Thai Police Department and the international standards, as well. Therefore, the recommendations are; the male investigators’ attitude should be adjusted to understand the female rape victims by specific training causes and the female rape victims should be informed about the due process of investigation in all cases of litigation